Urban green spaces and their impact on health and well-being: A case study of Tirana, Albania - Kruja, Samel; Diko, Olta Braçe; Garrido-Cumbrera, Marco (International Journal of Innovative Research and Scientific Studies, 2025)
Urban green spaces (UGS) play a vital role in fostering physical health, mental well-being, and social connectivity, particularly in rapidly urbanizing environments. This study examines the relationship between access to UGS and health outcomes in Tirana, Albania a city undergoing significant urban transformation. Employing a mixed-methods approach, we conducted a comprehensive survey with 493 respondents to assess the impact of UGS usage on self-reported health, well-being, and clinical depression. Statistical analyses revealed that frequent and quality interactions with UGS were associated with better mental health, increased physical activity, and stronger social bonds. Conversely, individuals reporting poor access to or negative perceptions of UGS quality experienced diminished well-being and higher incidences of depression. This study underscores the urgent need for urban planning policies that prioritize equitable distribution and enhancement of green spaces. By addressing these challenges, cities like Tirana can leverage UGS to enhance urban resilience, promote public health, and create more inclusive and livable environments.